3000 proverbs : accurate reliable convenient - Phillips, Sam. (New Delhi : Goodwill Publishing House)
The book 3000 Proverbs by Sam Phillips is a unique collection of some most popular proverbs used in everyday life. Proverbs included in this book are very useful for everyone, as they would add grandeur verbal and written communication. With all its uniqueness, the book is a must for all including common learners, students, teachers, authors, journalists and so forth.
Keywords: Proverbs, English